Disability Inclusion in Disaster Risk Management - Assessment in the Caribbean Region - World Bank (Washington, DC: World Bank, 2022)
Persons with disabilities make up just one of many groups in society that are systematically marginalized and disadvantaged. Gender, ethnic and religious diversity, poverty, age, homelessness, levels of education and literacy, gender preference and diversity, and geographic isolation are just some of the characteristics that can define social exclusion. The World Bank and the Global Facility for Disaster Reduction and Recovery (GFDRR), with support from the Canadian government, have established the Canada–Caribbean Resilience Facility (CRF) as a single-donor trust fund aimed at achieving more effective and coordinated gender-informed climate-resilient preparedness, recovery, and public financial management practices in nine targeted CRF-eligible countries. The CRF is supporting, disability inclusive disaster risk management (DRM) as an essential element in building this societal resilience. The primary purpose of this assessment is to understand gaps better in the inclusion of persons with disabilities in national disaster risk management (DRM) and climate resilience (CR) processes and strategies in Antigua and Barbuda, Belize, Dominica, Grenada, Guyana, Jamaica, Saint Lucia, Saint Vincent and the Grenadines, and Suriname. The report is based on the recognition that collectively people with disabilities are systematically marginalized and excluded from full and equal participation in society and societal processes. Primarily, the reasons are barriers to access that are both structural and nonstructural. These barriers can be removed or mitigated through effective social policy, implementation of existing norms and standards, and public will. The assessment will provide recommendations that make preparedness and recovery efforts more disability inclusive.